Unilateral versus bilateral pedicle screw fixation in lumbar fusion: A systematic review of overlapping meta-analyses - Zhao, Yachao (PLoS One, 2019)
OBJECTIVES: To carry out a systematic review on the basis of overlapping meta-analyses that compare unilateral with bilateral pedicle screw fixation (PSF) in lumbar fusion to identify which study represents the current best evidence, and to provide recommendations of treatment on this topic. METHODS: A comprehensive literature search in PubMed, Embase, and the Cochrane Library databases was conducted to identify meta-analyses that compare unilateral with bilateral PSF in lumbar fusion. Only meta-analyses exclusively covering randomized controlled trials were included. Study quality was evaluated using the Oxford Levels of Evidence and Assessment of Multiple Systematic Reviews (AMSTAR) instrument. Then, the Jadad decision algorithm was applied to select the highest-quality study to represent the current best evidence. RESULTS: A total of 9 studies with Level II of evidence fulfilled the eligibility criteria and were included. The scores of AMSTAR criteria for them varied from 5 to 9 (mean 7.78). The current best evidence detected no significant differences between unilateral and bilateral PSF for short-segment lumbar fusion in the functional scores, length of hospital stay, fusion rate, and complication rate. However, unilateral PSF involved a remarkable decrease in operative time and blood loss but increase of cage migration when compared with bilateral PSF. CONCLUSIONS: According to this systematic review, unilateral PSF is an effective method of fixation for short-segment lumbar fusion, has the advantages of reduced operative time and blood loss over bilateral PSF, but increases the risk of cage migration.